2020
DOI: 10.1200/jco.2020.38.15_suppl.e23527
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of YAP/ TAZ by statins to improve survival in epithelioid hemangioendothelioma (EHE).

Abstract: e23527 Background: EHE is a rare soft tissue tumor of endothelial origin. It is distinguished by the pathognomonic WWTR1-CAMTA1 fusion (WWTR1 is the gene symbol for TAZ) seen in 90% of the tumors. YAP1-TFE3 fusion is less common and seen in 10% of the tumors. YAP and TAZ are critical downstream effectors of the Hippo pathway that regulate tumor development, progression, invasion and metastasis by modulating the expression of many Hippo pathway targets. Recent studies have shown that inhibition of HMG-CoA redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We further showed that LATS1/2 regulate the subcellular localization of TAZ-CAMTA1 and that pharmacological intervention that is known to affect YAP/TAZ activity, such as statin treatment, could inhibit the activity of the TAZ-CAMTA1 fusion protein. Indeed, a retrospective analysis of patients with EHE showed that statin use was associated with increased survival, although the underlying mechanism was not investigated (Subramaniam et al 2020). Together, these findings suggest that mechanisms that activate Hippo signaling and/or inhibit YAP/ TAZ activity may provide a new avenue of therapy to inhibit TAZ-CAMTA1 activity in patients with EHE.…”
Section: Discussionmentioning
confidence: 99%
“…We further showed that LATS1/2 regulate the subcellular localization of TAZ-CAMTA1 and that pharmacological intervention that is known to affect YAP/TAZ activity, such as statin treatment, could inhibit the activity of the TAZ-CAMTA1 fusion protein. Indeed, a retrospective analysis of patients with EHE showed that statin use was associated with increased survival, although the underlying mechanism was not investigated (Subramaniam et al 2020). Together, these findings suggest that mechanisms that activate Hippo signaling and/or inhibit YAP/ TAZ activity may provide a new avenue of therapy to inhibit TAZ-CAMTA1 activity in patients with EHE.…”
Section: Discussionmentioning
confidence: 99%
“…Statins, used as standard treatment against hypercholesterolemia, have been known to inhibit the YAP/TAZ pathway. The inhibition of the hydroxymethylglutaryl-coenzyme A (HMG-CoA) reductase and the mevalonate pathway have been demonstrated to regulate YAP activation [ 154 ]. Statins may affect YAP nuclear localization by inducing phosphorylation, cytoplasmic retention, degradation, and the target genes’ decreased transcription by TEA domains [ 155 ].…”
Section: Yap and Taz As Therapeutic Targetsmentioning
confidence: 99%
“…Driskill et al demonstrated, in a heterologous cell-line model, that simvastatin abrogates the anchorage-independent growth of TC-transformed cells and suppresses the expression of TC transcriptional targets, suggesting that the Mevalonate/Rho axis may regulate TAZ–CAMTA1 activity [ 92 ]. This work was further supported by a recent retrospective review from the MD Anderson Cancer Center, which aimed to identify whether prognosis was affected in EHE patients who were on statins for other indications [ 106 ]. This study showed a greater median survival among patients on statin therapy than among those not on statin therapy.…”
Section: Development Of Targeted Therapiesmentioning
confidence: 99%